THE USING OF CARD SORT LEARNING STRATEGY IN INCREASING RESPONSIBILITY AND ACHIEVEMENT IN FIQIH SUBJECT (Study in 10th grade at MA Negeri 01 Lebong) - Azwen Wahab; Wasidi Wasidi (UNIB Press, 2019)
The purposes of this research are to improve students’ responsibility and achievement in Fiqih towards card sort learning strategy. This research was classroom action research, conducted collaboratively between researchers themselves as teachers of the school in question, and another teacher as an observer. In the execution of this study using a card sort strategy to increase the responsibility and achievement of students who have felt still very low. The subjects of this study were students of class X IPS MAN I Lebong totaling 26 people. The data was collected using test, observation sheets, the data processing by the rate, and the students’ learning mastery of t - test. The results of this study indicate that (1) the use of the card sort strategy could increase the students’ responsibility; (2) the use of the card sort strategy could increase the students’ achievements; (3) the effectiveness of the card sort strategy could increase the students’ achievement in Fiqih subject.